Single-cell transcriptome sequencing revealing the difference in photosynthesis and carbohydrate metabolism between epidermal cells and non-epidermal cells of Gracilariopsis lemaneiformis (Rhodophyta) - Chen, Haihong; Hu, Yiyi; Li, Pingping; Feng, Xiaoqing; Jiang, Min; Sui, Zhenghong (Frontiers in Plant Science, 2022)
The allocation of photoassimilates is considered as a key factor for determining plant productivity. The difference in photosynthesis and carbohydrate metabolism between source and sink cells provide the driven force for photoassimilates’ allocation. However, photosynthesis and carbohydrate metabolism of different cells and the carbon allocation between these cells have not been elucidated in Gracilariopsis lemaneiformis. In the present study, transcriptome analysis of epidermal cells (EC) and non-epidermal cells (NEC) of G. lemaneiformis under normal light conditions was carried out. There were 3436 differentially expressed genes (DEGs) identified, and most of these DEGs were related to photosynthesis and metabolism. Based on a comprehensive analysis both at physiological and transcriptional level, the activity of photosynthesis and carbohydrate metabolism of EC and NEC were revealed. Photosynthesis activity and the synthesis activity of many low molecular weight carbohydrates (floridoside, sucrose, and others) in EC were significantly higher than those in NEC. However, the main carbon sink, floridean starch and agar, had higher levels in NEC. Moreover, the DEGs related to transportation of photoassimilates were found in this study. These results suggested that photoassimilates of EC could be transported to NEC. This study will contribute to our understanding of the source and sink relationship between the cells in G. lemaneiformis.